There's More Than One Way to Get a House: Housing Strategies in Panama - Michael Jacobs; William D. Savedoff (Inter-American Development Bank, Office of the Chief Economist, 1999)
This paper uses household data from two cities in Panama to evaluate the determinants of the tenure decision in the context of two models. The key factors explaining the decision to rent or own are those associated with the family`s lifecycle, while the choice between buying a complete house and progressive building is affected primarily by income and assets.
Keywords: 330; Immobilienmarkt; Grundbesitz; Panama